Application of the concept of "functionalities" in macroeconomic modelling frameworks - Insights for Austria and methodological lessons learned. EconTrans working paper #4 - Gabriel Bachner; Jakob Mayer; Laura Fischer; Karl W. Steininger; Mark Sommer; Angela Köppl; Stefan P. Schleicher (Austrian Institute of Economic Research (WIFO), 2021)
In order to meet the climate targets as set out in the Paris agreement - i.e., to stay "well below 2 êC" of global warming - a transformation of the socio-economic system towards climate neutrality is required. This transformation is connected to radical changes in most aspects of our daily lives, especially with respect to mobility and housing. This poses the questions of how well-being might change due to these changes and ultimately how to quantitatively measure such changes. In the present paper we make a first steps towards answering these fundamental questions. We do so by making use of the concept of energy services, or "functionalities", which take a demand and sufficiency perspective. To quantify effects, we operationalise this concept by using and extending existing macroeconomic models (Input-Output and Computable General Equilibrium). In terms of results we provide standard economic indicators but contrast them with - in our view - more relevant indicators, such as a more comprehensive measure for well-being, as well as distributional effects and co-benefits. Our results clearly show increases in well-being emerging from the climate neutral transformation, whereas conventional indicators such as GDP are declining. We thus demonstrate the importance of looking at the "right" indicators, when assessing socio-economic effects of climate policy and at the same time provide a concrete alternative to state-of-the-art modelling approaches.
Keywords: 330